Entrepreneurial Challenges faced by Women - Shubham Bansal (International Journal of Advanced Science and Technology, 2020)
In 21st century, women still face numerous challenges, be it stereotyping in the field of entrepreneurship, which we will discuss in the research paper ahead, or confining women to four walls of the home for domestic chores. Majority of the women population in our country are not allowed to follow their passion or work towards their dream. Slowly, but definitely things are changing now. The world has started recognizing that women are as talented as men in the aspects of social as well as economic growth of the country. In India, entrepreneurship was considered a male dominated field, but for a change, women entrepreneurial drive has become an integral part of the economic development. Due to change in the mindsets, government initiatives and changes in the social environment, people have become comfortable when they see women leading the key roles. Also, government has taken major initiatives which help provide women support in the roles of entrepreneurship which further helps in the economic development of India. This paper discusses about the challenges faced by women as an entrepreneur in India and the data points to show how true those challenges are in the real world. The research is based on quantitative method from the primary research giving the paper a better sense of reliability and accuracy.